Literature and Culture in Late Byzantine Thessalonica. - Russell, Eugenia, 1976- (Bloomsbury Publishing, 2013)
The 'long' fourteenth century perhaps can be seen as Thessalonica's heyday. Alongside its growing commercial prowess, the city was developing into an important centre of government, where members of the Byzantine imperial family of the Palaiologoi ruled independently under full imperial titles, striking coinage and following an increasingly autonomous external policy. It was also developing into a formidable centre for letters, education, and artistic expression, due in part to Palaiologan patronage. This volume sets out the political and commercial landscape of Thessalonica between 1303 and 1.